(untitled) (Mugda Medical College Journal, 2025)
The diffuse parenchymal lung diseases (DPLDs) are a heterogeneous group of conditions affecting the pulmonary parenchyma (interstitial) and/or alveolar lumen. Since DPLD in overlap syndromes has a poor prognosis, extensive work up should be performed even when clinical evidence of only one autoimmune disease is present. DPLD is a frequent manifestation of connective tissue diseases (CTDs), with incidence and prevalence variously assessed in the literature but reported in up to 30% of patients, with higher frequency in rheumatoid arthritis (RA) and systemic sclerosis (SSc). However, Sjogren’s syndrome (SS) is a chronic inflammatory disease characterized by lymphocytic infiltrates in the exocrine glands, mainly the salivary and lacrimal glands. DPLD is found in 3-11% of the patients with primary Sjogren’s syndrome, often leading to life-threatening complications. When combined, the diagnosis is often missed or delayed, which can lead to an increased incidence of long-term morbidity and mortality. We present an interesting case of DPLD due to RA-SSc overlap syndrome and Sjogren syndrome – a 53-year-old non-diabetic, normotensive, non-smoker, cotton-wool cloth weaver, married, Muslim female presented with progressively increasing dry, distressing non-productive cough for 3 years which was persistent throughout the day without any seasonal or diurnal variation. She complaints of insidious onset, gradually progressive breathlessness, with mMRC grade-3 at present from initial mMRC grade-0. There was no history of orthopnoea, palpitation, chest pain or any swelling of body. She also complaints of symmetrical inflammatory polyarthritis for 6 months involving small joints of hands, wrist, elbow, feet; not associated with joint swelling, oral ulcer, photosensitivity. She developed painless, non-itchy salt and pepper skin pigmentation along with partly scaly over forehead, back of chest, around neck, upper and lower limbs but no muscle aches and proximal myopathy. We emphasized on inter-professional consultation in the diagnosis and treatment of such a rare case. Mugda Med Coll J. 2024; 7(2): 139-143